Evaluation of reports received on a digital platform for monitoring and self-care of individuals facing the COVID-19 pandemic in Brazil: Contributions to public health - Luiz Ricardo Albano dos Santos; Luana Michelly Aparecida Costa dos Santos; Guilherme José Aguilar; Wilbert Dener Lemos Costa; Dantony de Castro Barros Donato; Valdes Roberto Bollela; Alan Maicon de Oliveira (Elsevier, 2024)
Objectives: To evaluate the contribution of the digital platform "Meu Diário de Quarentena (MDQ)'' or My Quarantine Diary concerning the monitoring and self-care of individuals with COVID-19 in Brazil. And to analyze the epidemiological and clinical characteristics related to the disease and the users who adhered to the support provided by MDQ. Methods: MDQ was developed by a multidisciplinary team and offered to the general population to provide self-care and health education during the COVID-19 pandemic, relying on users' self-reporting of information (such as signs and symptoms, pre-existing health conditions, and medications used during quarantine). The outcomes were measured, and the web app's support experience for public health was reported. Results: MDQ had 2439 active users on the platform, with 485 (19.9 %) self-reporting a COVID-19 diagnosis, mostly from individuals in the southeastern region of Brazil (56.5 %). The most common pre-existing health condition reported was related to circulatory system diseases. The most frequent reported signs and symptoms included headache, cough, myalgia, nasal congestion and muscle weakness. Corticosteroids, multivitamins, and anti-inflammatories were the most used medications during the pandemic period. There were several reports related to how users were feeling during the pandemic, and among these reports, negative feelings toward isolation stood out, such as "feeling lonely", "anxious", and "feeling useless". A significant association was found between sex (p < 0.001) and age (p < 0.001) in relation to self-reported cases of COVID-19. Conclusions: The use of MDQ during extended quarantine was an easy and interesting way of interaction and support for people during COVID-19 pandemic.